Is there a “renal-pulmonary syndrome” in rheumatoid arthritis? - A. V. Gordeev; E. A. Galushko; E. V. Matyanova; E. V. Pozhidaev; E. G. Zotkin; A. M. Lila (Современная ревматология, 2024)
Objective: to compare the course of “rheumatoid disease” in multimorbid patients with and without interstitial lung disease (ILD).Material and methods. Two groups were formed of 1034 patients with active rheumatoid arthritis (RA) who met the 2010 ACR/EULAR criteria: one group with ILD identified by high-resolution computed tomography of the lungs (n=82) and another – without ILD (n=900). In all patients, estimated glomerular filtration rate (eGFR) was determined using the Cockroft–Gault formula. The presence and stage of chronic kidney disease (CKD) was assessed depending on the eGFR level: stage I CKD was diagnosed in eGFR <89 ml/min, stage II (subclinical) – 60<eGFR <89 ml/min, stage IIIa (clinical) – 45<eGFR<59 ml/min and IIIb – 30<eGFR<45 ml/min.Results and discussion. Arterial hypertension (p=0.004), cerebrovascular disease (p=0.0001), diabetes mellitus (p=0.04), obesity, psoriasis (p=0.009) and stage II–III CKD (p=0.04) were more frequently observed in the group with ILD.Conclusion. The combination of CKD and ILD frequently found in patients with RA and the known similarity and close interrelationship of the pathogenesis of these diseases, suggest a type of “renal-pulmonary syndrome” associated with a specific variant of RA.